Sauvignon Blanc Wine: Contribution of Ageing and Oxygen on Aromatic and Non-aromatic Compounds and Sensory Composition : A Review - Coetzee, C.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2016)
Oxidation and the capacity for sufficient ageing potential of white wines are constant problems for winemakers worldwide. In general, it is accepted that certain grape varieties are especially sensitive to oxidation, suggesting that some of the chemical components key to their sensory attributes are strongly modulated by oxygen exposure. Sauvignon blanc is a well-documented example of an oxygen-sensitive wine, and understanding the stability of various compounds is crucial in order to preserve the fresh and fruity characters of Sauvignon blanc wines while preventing the formation of off-odours over a long period of time. Compounds such as the volatile thiols and methoxypyrazines are key aroma compounds responsible for the typical Sauvignon blanc aroma, while other aroma compounds, such as esters, alcohols and acids, can also contribute to the wine aroma. Oxidation-related compounds (such as aldehydes) can occur under certain conditions and it is essential to understand the chemistry behind oxidation to control and manage the development of various characteristics in wine. The sensory interactions occurring between various compounds (both aromatic and non-aromatic) are also important due to enhancing or suppressive effects that can mask certain aroma nuances. This review focuses on the stability of certain compounds of Sauvignon blanc wines during oxidation and ageing and how it affects the aromatic and non-aromatic composition of these wines.